The Effect of Temperature on Dynamic Characteristics of Frozen Clay under Principal Stress Rotation - Bin-Long Zhang; Da-Yan Wang; Zhi-Wei Zhou; Wei Ma; Le-Le Lei (Advances in Materials Science and Engineering)
The foundation soil is always subjected to complex stress, including continuous rotation of the principal stress caused by traffic and earthquake loads. To comprehend the dynamic characteristics of frozen clay under complex stress sate, including continuous rotation of the principal stress, this study investigates the effect of temperature on the dynamic characteristics of frozen clay under principal stress rotation using a frozen hollow cylinder apparatus (FHCA-300). The test results reveal that the cumulative plastic strain of frozen clay samples exponentially increases with the rising of temperature under principal stress rotation. The influence of temperature is more profound with a high cyclic stress ratio (CSR). A decrease in temperature can improve the stiffness of the frozen clay, reduces its energy dissipation, and enhances its ability to resist dynamic loading. However, the principal stress rotation phenomenon may aggravate the damage of frozen clay and increase the energy dissipation and reduces its ability to resist dynamic loading. Based on the experimental data, an empirical expression was proposed to describe the coupling influence of CSRs and temperature on the axial resilient modulus of frozen clay, which can predict the development of axial resilient modulus under different thermal-mechanical conditions.